Therapist competence, comorbidity and cognitive-behavioral therapy for depression. - Kuyken, W; Tsivrikos, D (2009)
BACKGROUND: Therapist competence has consistently been associated with therapy outcomes, although the nature of this relationship varies considerably across studies. METHOD: In a naturalistic process-outcome study, 69 clients presenting with depression were treated by 1 of 18 cognitive-behavioral therapists in a 'real world' outpatient clinic. Using triangulated measures of therapists' competence, we hypothesized that greater therapist competence would be associated with improved cognitive-behavioral therapy (CBT) outcomes for clients diagnosed with depression. We hypothesized that the variation in the research to date on therapist competence and CBT for depression outcomes may be due to the moderating effects of complexity of client presentation, in terms of comorbidity. RESULTS: We replicated the previous finding that comorbidity compromises CBT for depression outcomes, but found that greater therapist competence was associated with improved outcomes, regardless of clients' comorbidity. CONCLUSIONS: Therapist competence is associated with improved therapy outcomes, and therapists who are more competent have better patient outcomes regardless of the degree of patient comorbidity.